«Den verkliga festen, som är dödstyst» – Tomas Tranströmers "Blåsipporna" und das Heilige - Seiler, Thomas (Folia Scandinavica Posnaniensia, 2021)
Tranströmer’s prose poem Blåsipporna ("The Liverleafs") is rather cryptic. By reading the text in the light of Kant’s theory of the sublime and by focusing on its mysterious and paradoxical aspects, this essay seeks to unveil the poem’s hidden eschatology. The poem’s transcendence is the result of the rhetorical and literary devices the poet is using to depict an ecstatic experience. Such an experience is beyond rationality, hence the wording’s irrationality. In addition, the poem addresses silence, as the experience of ecstasy can never be expressed by words. Thus, "Blåsipporna" is a piece of art and a sacred text at the same time.